Control para el seguimiento del punto de máxima potencia en sistemas fotovoltaicos bajo condiciones de sombra parcial. (2024)
In this project, a control system is designed for maximum power point tracking (MPPT) in a photovoltaic array under partial shading conditions. Based on the literature review, the following hypothesis is proposed: to achieve maximum power transfer in a photovoltaic system under partial shading, both the type of photovoltaic array connection and the control that ensures the delivered voltage must be considered.